Relationship between Helicobacter pylori Infection and Gastroesophageal Reflux Disease (GERD) - Halim, Silvikarina Erfanti Dewi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Background: Helicobacter pylori infection is a gastrointestinal infection that affects about 50% of the world's population, however, its prevalence varies across geographic areas. The actual relationship of H. pylori with gastroesophageal reflux disease (GERD) is still unclear because some studies report a high prevalence of H. pylori in GERD patients, but some studies report the opposite. This study aims to determine the relationship between H. pylori infection and GERD and the prevalence of Helicobacter pylori infection in GERD patients at Eka Hospital Pekanbaru.Method: This study was a cross-sectional study of GERD patients who had undergone endoscopy at Eka Hospital Pekanbaru from January 2021 to December 2022. There were 219 patients. This research was then analyzed with the chi-square test using SPSS version 22.Results: A total of 219 GERD patients met the criteria for this study. 108 of them were positive for H. pylori from the results of endoscopic biopsies. The prevalence of GERD patients infected with H. pylori is 49.3%. 108 of them were positive patients, 14 (13%) GERD patients were ≥ 60 years old and 94 (87%) were 60 years old. Of the 108 positive patients, 53 (49.1%) were male, 55 (50.9%) were female. Where age and gender did not significantly increase the risk of H. pylori infection (p 0.05). The most common endoscopic biopsy finding is chronic erosive gastritis.Conclusion: Although the prevalence of GERD patients infected with H. pylori was quite large (49.3%), there was no significant association between GERD patients and the incidence of H. pylori infection.